Pengaruh PH Terhadap Evesiensi Air Limbah Grey Water Dengan Media Honeycomb - Febri Maharani Putri; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Domestic wastewater contributes greatly to water pollution in urban areas because the application of treatment is not optimal. This research with aerobic biofilter system with plastic media honeycomb was done to process domestic wastewater. The purpose of this study was to study the influence of recirculation and aeration (reactor A), aeration (reactor B), recirculation (reactor C), and without recirculation and aeration (reactor D) on the decrease in pH concentration in wastewater. Reactors are prepared with each reactor containing honeycomb media. Conditioning and growth of microorganisms in the reactor is carried out for 14 days until the biofilm is formed. The optimum values of pH removal in the four reactors with a stay of 12 hours were pH 90.1%, 93.7%, 75.8%, 67.9%. The results showed that reactor B with the use of an aeration system is effective in lowering the concentration of pollutants in domestic wastewater. Keywords: domestic waste, biofilter aerobic, honeycomb, pH